Decoupled Unipolar Hysteresis Current Control for Single-Phase Grid-Tied Inverter Without Current Zero-Crossing Distortion - Rui Xie; Qingfa Zeng; Fei Yang; Bin Lin; Ouyang Xu; Yuanbin He (IEEE Access, 2024)
A digital controlled unipolar hysteresis current control strategy applied to the single-phase grid-connected inverter is studied in the paper. In view of the problem of current zero-crossing distortion in the traditional unipolar hysteresis current control based on finite state machines (FSM), a new unipolar hysteresis current control strategy based on current decoupling is proposed. By introducing a virtual zero-sequence current, the single-phase full-bridge inverter is decoupled into two independent half-bridge inverter units, which are controlled by two bipolar hysteresis current control loops under the constraints of a finite state machine. Therefore, the operation rules of the FSM ensure the frequency doubling output of the unipolar modulation, and the virtual two-phase decoupled current eliminates the zero-crossing distortion problem of inverter output current. Finally, the effectiveness and feasibility of the proposed method were verified by building a 1kW single-phase full-bridge grid-connected inverter in the laboratory.